Демографічний розвиток населення середньобузької локальної групи розвинутого Трипілля - Тарапата, Д.О. (Археологія, 2014)
Проаналізовано тенденції демографічного розвитку населення середньобузької локальної групи Кукутень-Трипілля для відтворення міграційних процесів. Проанализированы поселения Среднего Побужья с целью реконструкции тенденции демографического развития населения среднебугской локальной группы. Основное внимание уделено миграционным процессам. Миграции идентифицированы на основе сопоставления суммарного количества построек синхронных поселений и изменчивости их керамических комплексов.
Сравнение схем относительной хронологии поселений среднебугской группы (С.А. Гусев) и памятников влади мировскотомашовской линии западнотрипольской культуры в Буго-Днепровском междуречье (А.В. Дяченко и Ф. Ме нотти) позволило уточнить относительную хронологию поселений Среднего Побужья. Выделены две фазы развития поселений ворошиловского типа, первая из которых поделена на две ступени, две фазы развития поселений немировского типа и четыре — куриловского типа. Кроме того, подтверждено мнение С.А. Гусева относительно отдельных типов орнамента и орнаментальных композиций как хроноиндикаторов. Керамика поселений первой фазы ворошиловского типа (Вербивка I, Ворошиловка, Селище) характеризуется углубленным орнаментом в разных пропорциях, углубленным орнаментом с заполнением белой пастой. Сосуды второй фазы (Сосны) украшали только росписью. Углубленный орнамент вновь появляется на керамике поселений первой фазы немировского типа (Вербивка II, Крыштоповка) и исчезает ко второй (Каролина, Немиров). Для росписи сосудов первой фазы куриловского типа (Лысогирка) характерна s-видная петля в упрощенном виде, которая уже неизвестна в орнаменте керамики второй фазы (Куриловка, Кожухов). Поздние ворошиловские памятники синхронны ранним немировским, а городищенские — ранним куриловским.
Смена типов памятников и формирование крупных поселений региона обусловлено миграционными волнами западнотрипольского населения из Поднестровья. Отметим одинаковые тенденции для памятников Среднего Побужья и Буго-Днепровского междуречья. Наибольшие поселения немировского типа (Вербивка II, Крыштоповка) датируются первой фазой развития данного типа, как и наибольшие синхронные им поселения Буго-Днепровского междуречья Небелевка и Валява, относящиеся к первой фазе развития небелевской группы. Крупные поселения Куриловка, а также Доброводы и Чичиркозовка относятся ко второй фазе развития куриловского типа и второй фазе томашовской группы соответственно. Аналогичные тенденции можно также отметить для синхронных па мятников чечельницкой группы (эпонимное поселение достигает около 56 га). Очевидно, на первой фазе развития куриловского типа и первой фазе томашовской группы в два названных региона проникали небольшие группы мигрантов с запада, а в последующем сюда продвинулось сравнительно многочисленное население.
В целом демографическое развитие населения среднебугской группы описывается дискретным аналогом s-видной кривой. Это свидетельствует о росте населения под воздействием ограничивающих факторов. Для вре мени миграций характерны аномально высокие тенденции в росте количества построек, а, значит, и увеличении численности населения. Trypillian settlements at the Buh river middle region are located in the centre of distribution of KukuteniTrypillya cultural assemblage sites and are of a great importance in its study. The paper is devoted to the tendencies of demographic development of Middle Buh local group population. The main attention is paid to the analysis of migration processes. Migrations are identified based on comparison of total number of structures at synchronous settlements and variety of their ceramic assemblages.
Comparison of relative chronology schemes of the Middle Buh group settlements (s.O. husiev) and of monuments of volodymyrivkaTomashivka line in Western Trypillya culture at the area between the Buh and Dnipro rivers (O.v. Dyachenko and F. Menotti) allowed the author to specify the relative chronology of settlements at the Buh river middle region. Two phases of voroshylivka type settlements are singled out, first of which is divided into two stages, two phases of nemyriv type settlements and four ones of Kurylivka type settlements. in addition, the author managed to confirm s.O. husiev’s point of view concerning the understanding of separate types of ornaments and ornamental compositions as chronological indicators. Ceramics from settlements of voroshylivka type first phase (verbivka i, voroshylivka, selyshche) is characterized by deep ornament in various proportions and by deep ornament with white dope filling. The second type vessels (sosny) were decorated by paint only. Deep ornament appears again on the ceramics at the first phase settlements of nemyriv type (verbivka ii, Kryshtopivka), vanishing only at the second phase (Karolina, nemyriv). paintings on the first phase vessels of Kurylivka type (Lysohirka) are peculiar by the sshaped simplified loop which is already not known in the ornament of the second phase (Kurylivka, Kozhukhiv). The late voroshylivka type sites are synchronous to the early nemyriv ones, while horodyshche type sites to the early Kurylivka ones.
Change of monuments types and creation of large settlements at the region are stipulated for the migration waves of the Western Trypillian population from the Dnister river region. it is important to note the equal tendencies for the sites at the Buh river middle region and at the area between the Buh and Dnipro rivers. The largest settlement of nemyriv type (verbivka ii, Kryshtopivka) are dated by the first phase of this type development, as well as the largest synchronous settlements nebelivka and valiava at the area between the Buh and Dnipto rivers belong to the first phase of nebelivka group development. Large settlements Kurylivka and also Dobrovody and Chychyrkozivka belong correspondingly to the second phase of Kurylivka type development and to the second phase of Tomashivka phase. equal tendencies can be also noted for synchronous sites of Chechelnyk group (eponymous settlement reaches up to 56 ha). apparently, at the first phase of Kurylivka type development and the first phase of Tomashivka group small groups of migrants from the west came to the two mentioned regions, and later comparatively numerous population moved here.
as a whole, demographic development of the Middle Buh group population is described by discrete analogue of the sshaped curve. This fact testifies to the increase in population under the influence of limiting factors. The period of migrations is characterised by abnormally high tendencies in the raise of structures number, and consequently, in the raise of population).